An energy storage power supply with efficient heat dissipation function
By using bismuth molybdate @ palma wax microsphere phase change material, the problems of low thermal conductivity and easy leakage in energy storage power supply are solved, achieving efficient heat dissipation and battery protection.
Patent Information
- Application Number
- CN202410493771.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-23
AI Technical Summary
The phase change materials of existing energy storage power supplies have problems such as low thermal conductivity and easy leakage, resulting in poor heat dissipation and even causing damage to the battery.
Using bismuth molybdate @ palma wax microspheres as phase change material, and using polyethylene glycol, sodium tartrate and sodium polystyrene sulfonate as structural guides, the shell core microspheres are prepared, which improves the thermal conductivity of the material. and leak-proof.
It achieves higher latent heat storage, less leakage and high thermal conductivity, and is suitable for efficient heat dissipation of energy storage power supplies, protecting the battery while extending the service cycle.
Smart Images

Figure CN118398953B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of energy storage power supplies, and in particular to an energy storage power supply with a high-efficiency heat dissipation function. Background Art
[0002] Energy storage power supply is a special type of power supply that is used to store electrical energy and release it when needed. Unlike disposable power supplies, energy storage power supplies can be charged and discharged multiple times to achieve long-term energy storage and supply. It is a very widely used power supply.
[0003] In the prior art, due to the large power capacity of the energy storage power supply, both the power supply and the circuit board will generate heat during use. In order to ensure the safety of the use of the energy storage power supply, heat is often dissipated inside it. The heat dissipation methods of the energy storage power supply mainly include air cooling, liquid cooling, phase change material cooling, and heat pipe cooling. Air cooling technology is an extension of air conditioning, while liquid cooling technology is borrowed from electric vehicles. Air cooling has the advantages of mature solutions, simple structure, easy maintenance, and low cost, but it is usually used in occasions with low heat generation rate, such as communication base stations, small ground power stations and other areas with low power density. The liquid cooling system has the characteristics of high heat transfer coefficient, large specific heat capacity, good cooling effect, good sustainability under different environments, compact structure, and small footprint.
[0004] Phase change, that is, the transition of a substance from one phase to another, the temperature remains almost unchanged during the change process, but there are obvious heat absorption and heat release phenomena. The combination of heat absorbed and released during the whole process is called the latent heat of phase change. In nature, there are many materials with small temperature changes but large heat absorption and release during phase change. If such materials have good thermal conductivity, they can be used in many thermal management occasions and are usually called phase change materials. Phase change material cooling is to use its own phase transition to achieve the purpose of battery heat dissipation. For batteries, the biggest factor affecting the heat dissipation effect is the phase change material itself. The higher the heat transfer coefficient of the material, the better the cooling effect, and vice versa. However, the existing phase change materials used in batteries not only have the defect of low thermal conductivity, but also some phase change materials are not tightly coated during the preparation process, resulting in leakage, which not only fails to achieve the heat dissipation effect, but also has a damaging effect on the battery itself. Summary of the invention
[0005] In view of the problems existing in the prior art, an object of the present invention is to provide an energy storage power supply with a high-efficiency heat dissipation function.
[0006] The purpose of the present invention is achieved by the following technical solutions:
[0007] A energy storage power supply with efficient heat dissipation function comprises an energy storage battery pack and a heat dissipation shell coated on the surface of the energy storage battery pack; wherein the heat dissipation shell is a hollow cavity structure, and the interior of the cavity structure is filled with a phase change material; the phase change material is bismuth molybdate@palm wax microspheres.
[0008] Preferably, the heat dissipation housing is made of aluminum or stainless steel.
[0009] Preferably, the method for preparing the phase change material comprises:
[0010] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 68-75° C., then add palm wax, sodium tartrate and sodium polystyrene sulfonate in sequence, keep them warm and stir for half an hour, and then shear and disperse them to form a palm wax emulsion;
[0011] S2, weighing bismuth trichloride and dissolving it in deionized water to obtain a bismuth trichloride solution; weighing sodium molybdate and dissolving it in deionized water to obtain a sodium molybdate solution;
[0012] S3, heating the palm wax emulsion to 80-90°C, adding bismuth trichloride solution dropwise thereto, keeping warm and stirring for 2-4h after the addition is completed, then adding sodium molybdate solution dropwise, keeping warm and stirring again for 2-4h after the addition is completed, then cooling the system, aging it, filtering and collecting the solid, washing and drying it to obtain bismuth molybdate@palm wax microspheres.
[0013] Preferably, in S1, the polyethylene glycol is one of PEG-200, PEG-300 and PEG-400.
[0014] Preferably, in S1, the palm wax is carnauba wax T3FF.
[0015] Preferably, in S1, the sodium tartrate is L-sodium tartrate.
[0016] Preferably, in S1, the molecular weight of sodium polystyrene sulfonate is 30,000-50,000.
[0017] Preferably, in S1, the mass ratio of polyethylene glycol, palm wax, sodium tartrate, sodium polystyrene sulfonate and deionized water is 0.3-0.8:6-10:0.42-0.63:1-1.5:100.
[0018] Preferably, in S1, the shear dispersion is carried out in a high-speed shear disperser at a speed of 8000-12000 rpm for 5-10 min.
[0019] Preferably, in the bismuth trichloride solution of S2, the mass ratio of bismuth trichloride to deionized water is 5.36-10.72:100.
[0020] Preferably, in the sodium molybdate solution of S2, the mass ratio of sodium molybdate to deionized water is 3.5-7:100.
[0021] Preferably, in S3, the mass ratio of the bismuth trichloride solution, the sodium molybdate solution and the palm wax emulsion is 0.92-1.16:1.12-1.25:1.
[0022] Preferably, in S3, the system is cooled to 25-40°C, and the aging treatment is carried out by stirring at a temperature of 25-40°C for 15-20h.
[0023] Preferably, in S3, washing is performed by washing with water at least three times, and drying is performed in a vacuum oven at 25°C.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention prepares a phase change material for heat dissipation of energy storage power supply, and the phase change material is a shell-core type bismuth molybdate @ palm wax microsphere. Compared with conventional phase change materials, the phase change material prepared by the present invention not only has higher latent heat storage, but also has the advantages of not easy to leak and high thermal conductivity. Therefore, it is suitable for use in energy storage power supply to replace traditional phase change materials, thereby achieving the effect of efficient heat dissipation and battery protection.
[0026] 2. The phase change material prepared by the present invention is a core-shell microsphere material with palm wax having high enthalpy value and excellent stability as the core and bismuth molybdate generated in situ as the shell. In the synthesis process of the phase change material, polyethylene glycol is used as a surfactant, and sodium tartrate and sodium polystyrene sulfonate are used as structure directing agents to promote the fusion of palm wax droplets and the growth of nanocrystals of bismuth molybdate layer to form a core-shell microsphere material.
[0027] 3. In the synthesis process of phase change materials, sodium tartrate is used as dicarboxylate and sodium polystyrene sulfonate is used as polymer sulfonate. The two complement each other as structure directing agents, which not only realizes the morphology control of microspheres, but also promotes the closer growth of bismuth molybdate layer nanoparticles, thereby improving the anti-leakage and thermal stability of the phase change material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0029] Figure 1 Schematic diagram of SEM of bismuth molybdate@palm wax microspheres prepared in Example 1 of the present invention.
[0030] Figure 2It is an infrared schematic diagram of bismuth molybdate@carnauba wax microspheres prepared in Example 1 of the present invention and carnauba wax of Comparative Example 1. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0032] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0033] The present invention will be further described below in conjunction with the following examples.
[0034] Example 1
[0035] An energy storage power supply with efficient heat dissipation function includes an energy storage battery pack and a heat dissipation shell coated on the surface of the energy storage battery pack; the heat dissipation shell is made of an aluminum shell. The heat dissipation shell is a hollow cavity structure, and the cavity structure is filled with a phase change material; the phase change material is bismuth molybdate @ palm wax microspheres.
[0036] The preparation method of the phase change material comprises:
[0037] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 72°C, and then add carnauba wax T3FF (CW), sodium L-tartrate and sodium polystyrene sulfonate (molecular weight 40,000) in sequence. The mass ratio of polyethylene glycol, carnauba wax, sodium tartrate, sodium polystyrene sulfonate and deionized water is 0.5:8:0.52:1.3:100. After keeping warm and stirring for half an hour, pour them into a high-speed shear disperser and perform shear dispersion at a speed of 10,000 rpm for 8 minutes to form a carnauba wax emulsion.
[0038] S2, weigh bismuth trichloride (BiCl3) and dissolve it in deionized water, the mass ratio of bismuth trichloride to deionized water is 8.04:100, and obtain a bismuth trichloride solution; weigh sodium molybdate (Na2MoO4) and dissolve it in deionized water, the mass ratio of sodium molybdate to deionized water is 5.25:100, and obtain a sodium molybdate solution;
[0039] S3, the palm wax emulsion is heated to 85 ° C, bismuth trichloride solution is added dropwise thereto, and the mixture is kept warm and stirred for 2-4 hours after the addition is completed, and then sodium molybdate solution is added dropwise. After the addition is completed, the mixture is kept warm and stirred for 3 hours again, and the mass ratio of bismuth trichloride solution, sodium molybdate solution and palm wax emulsion is 1.04:1.18:1. After that, the system is cooled to 30 ° C, kept warm and stirred for 20 hours, the product precipitation is aged, and then the solid is collected by filtration, washed with water at least three times, and dried in a vacuum oven at 25 ° C to obtain bismuth molybdate @ palm wax microspheres (BMO@CW).
[0040] Example 2
[0041] An energy storage power supply with efficient heat dissipation function includes an energy storage battery pack and a heat dissipation shell coated on the surface of the energy storage battery pack; the heat dissipation shell is made of a stainless steel shell. The heat dissipation shell is a hollow cavity structure, and the cavity structure is filled with a phase change material; the phase change material is bismuth molybdate @ palm wax microspheres.
[0042] The preparation method of the phase change material comprises:
[0043] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 68°C, and then add carnauba wax T3FF (CW), sodium L-tartrate and sodium polystyrene sulfonate (molecular weight 40,000) in sequence. The mass ratio of polyethylene glycol, carnauba wax, sodium tartrate, sodium polystyrene sulfonate and deionized water is 0.3:6:0.42:1:100. After keeping warm and stirring for half an hour, pour them into a high-speed shear disperser and perform shear dispersion at a speed of 8000rpm for 5min to form a carnauba wax emulsion.
[0044] S2, weigh bismuth trichloride (BiCl3) and dissolve it in deionized water, the mass ratio of bismuth trichloride to deionized water is 5.36:100, and obtain a bismuth trichloride solution; weigh sodium molybdate (Na2MoO4) and dissolve it in deionized water, the mass ratio of sodium molybdate to deionized water is 3.5:100, and obtain a sodium molybdate solution;
[0045] S3, the palm wax emulsion is heated to 80 ° C, bismuth trichloride solution is added dropwise thereto, and the mixture is kept warm and stirred for 2 hours after the addition is completed, and then sodium molybdate solution is added dropwise. After the addition is completed, the mixture is kept warm and stirred for 2 hours again, and the mass ratio of bismuth trichloride solution, sodium molybdate solution and palm wax emulsion is 0.92:1.12:1, and then the system is cooled to 25 ° C, kept warm and stirred for 15 hours, the product precipitation is aged, and then the solid is collected by filtration, washed with water at least three times, and dried in a vacuum oven at 25 ° C to obtain bismuth molybdate@palm wax microspheres.
[0046] Example 3
[0047] An energy storage power supply with efficient heat dissipation function includes an energy storage battery pack and a heat dissipation shell coated on the surface of the energy storage battery pack; the heat dissipation shell is made of an aluminum shell. The heat dissipation shell is a hollow cavity structure, and the cavity structure is filled with a phase change material; the phase change material is bismuth molybdate @ palm wax microspheres.
[0048] The preparation method of the phase change material comprises:
[0049] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 75°C, and then add carnauba wax T3FF (CW), sodium L-tartrate and sodium polystyrene sulfonate (molecular weight 40,000) in sequence. The mass ratio of polyethylene glycol, carnauba wax, sodium tartrate, sodium polystyrene sulfonate and deionized water is 0.8:10:0.63:1.5:100. After keeping warm and stirring for half an hour, pour them into a high-speed shear disperser and perform shear dispersion at a speed of 12000rpm for 10min to form a carnauba wax emulsion.
[0050] S2, weigh bismuth trichloride (BiCl3) and dissolve it in deionized water, the mass ratio of bismuth trichloride to deionized water is 10.72:100, and obtain a bismuth trichloride solution; weigh sodium molybdate (Na2MoO4) and dissolve it in deionized water, the mass ratio of sodium molybdate to deionized water is 7:100, and obtain a sodium molybdate solution;
[0051] S3, palm wax emulsion is warmed up to 80-90 DEG C, bismuth trichloride solution is added dropwise thereto, and after the addition is completed, the mixture is insulated and stirred for 2-4h, and then sodium molybdate solution is added dropwise. After the addition is completed, the mixture is insulated and stirred for 2-4h again. The mass ratio of bismuth trichloride solution, sodium molybdate solution and palm wax emulsion is 1.16:1.25:1, and the system is cooled to 40 DEG C afterwards, and the mixture is insulated and stirred for 20h to make the product precipitate aged, and then the solid is collected by filtration, washed with water at least three times, and dried in a vacuum oven at 25 DEG C to obtain bismuth molybdate@palm wax microspheres.
[0052] Comparative Example 1
[0053] A phase change material for energy storage power supply. The phase change material used in this comparative example is carnauba wax T3FF (CW).
[0054] Comparative Example 2
[0055] A phase change material for energy storage power supply, the preparation method is slightly different from that of Example 1, that is, in step S1, sodium L-tartrate is omitted and only sodium polystyrene sulfonate is added. Specifically:
[0056] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 72°C, then add carnauba wax T3FF (CW) and sodium polystyrene sulfonate (molecular weight 40,000) thereto in sequence, the mass ratio of polyethylene glycol, carnauba wax, sodium polystyrene sulfonate and deionized water is 0.5:8:1.82:100, keep warm and stir for half an hour, pour them into a high-speed shear disperser, and shear and disperse them at a speed of 10,000 rpm for 8 minutes to form a carnauba wax emulsion;
[0057] S2, prepare bismuth trichloride solution and sodium molybdate solution, the same as the process of Example 1;
[0058] S3. Prepare bismuth molybdate@palm wax microspheres in the same manner as in Example 1.
[0059] Comparative Example 3
[0060] A phase change material for energy storage power supply, the preparation method is slightly different from that of Example 1, that is, in step S1, sodium polystyrene sulfonate is omitted and only sodium L-tartrate is added. Specifically:
[0061] S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 72°C, then add carnauba wax T3FF (CW) and L-sodium tartrate thereto in sequence, the mass ratio of polyethylene glycol, carnauba wax, L-sodium tartrate and deionized water being 0.5:8:1.82:100. After keeping warm and stirring for half an hour, pour them into a high-speed shear disperser, and shear and disperse them at a speed of 10000 rpm for 8 minutes to form a carnauba wax emulsion;
[0062] S2, prepare bismuth trichloride solution and sodium molybdate solution, the same as the process of Example 1;
[0063] S3. Prepare bismuth molybdate@palm wax microspheres in the same manner as in Example 1.
[0064] Experimental example
[0065] The phase change materials prepared in Example 1 and Comparative Examples 1-3 were tested for thermal conductivity, heat absorption, and impermeability.
[0066] The calculation formula of encapsulation rate (E) is: Wherein, △H1 is the melting enthalpy of bismuth molybdate@palm wax microspheres, and △H2 is the melting enthalpy of carnauba wax.
[0067] The thermal conductivity was tested using a thermal conductivity tester, and the average value was taken after 5 tests.
[0068] The endothermicity is expressed based on non-isothermal detection and is expressed by the latent heat storage rate (R) at a DSC scan rate of 20°C / min, calculated as: Among them, △H is the melting enthalpy value; T1 is the end time of phase change, and T2 is the start time of phase change.
[0069] The anti-permeability is expressed by the leakage rate, the test temperature is 60℃, and the test time is 12h. The calculation formula for the leakage rate (L) test is: Among them, M1 is the initial mass, and M2 is the mass of paraffin seeped out at 12 hours.
[0070] The test results are shown in Table 1:
[0071] Table 1 Performance test results of different phase change materials
[0072]
[0073] It can be seen from Table 1 that the bismuth molybdate@palm wax microsphere phase change material prepared in Example 1 of the present invention has better thermal conductivity, higher latent heat storage rate and lower leakage rate, indicating that as a phase change material, it can achieve the effects of fast heat absorption, good thermal conductivity and low leakage, thereby playing a role of efficient heat dissipation in the energy storage power supply, and the effect of low leakage can extend its service life.
[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An energy storage power supply with efficient heat dissipation function, characterized in that: It includes an energy storage battery pack and a heat dissipation shell coated on the surface of the energy storage battery pack; wherein the heat dissipation shell is a hollow cavity structure, and the interior of the cavity structure is filled with a phase change material; the phase change material is bismuth molybdate @ palm wax microspheres; The preparation method of the phase change material comprises: S1. Weigh polyethylene glycol and deionized water, mix them, stir them thoroughly, heat them to 68-75° C., then add palm wax, sodium tartrate and sodium polystyrene sulfonate in sequence, keep them warm and stir for half an hour, and then shear and disperse them to form a palm wax emulsion; S2, weighing bismuth trichloride and dissolving it in deionized water to obtain a bismuth trichloride solution; weighing sodium molybdate and dissolving it in deionized water to obtain a sodium molybdate solution; S3, heating the palm wax emulsion to 80-90°C, adding bismuth trichloride solution dropwise thereto, keeping warm and stirring for 2-4h after the addition is completed, then adding sodium molybdate solution dropwise, keeping warm and stirring again for 2-4h after the addition is completed, then cooling the system, aging it, filtering and collecting the solid, washing and drying it to obtain bismuth molybdate@palm wax microspheres.
2. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: The heat dissipation housing is made of aluminum or stainless steel.
3. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In S1, polyethylene glycol is one of PEG-200, PEG-300, and PEG-400; palm wax is carnauba wax T3FF; sodium tartrate is L-sodium tartrate; and the molecular weight of sodium polystyrene sulfonate is 30,000-50,000.
4. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In the S1, the mass ratio of polyethylene glycol, palm wax, sodium tartrate, sodium polystyrene sulfonate and deionized water is 0.3-0.8:6-10:0.42-0.63:1-1.5:
100.
5. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In S1, the shear dispersion is carried out in a high-speed shear disperser at a speed of 8000-12000 rpm for 5-10 min.
6. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In the bismuth trichloride solution of S2, the mass ratio of bismuth trichloride to deionized water is 5.36-10.72:100; in the sodium molybdate solution of S2, the mass ratio of sodium molybdate to deionized water is 3.5-7:
100.
7. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In S3, the mass ratio of the bismuth trichloride solution, the sodium molybdate solution and the palm wax emulsion is 0.92-1.16:1.12-1.25:
1.
8. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In S3, the system is cooled to 25-40°C, and the aging treatment is carried out by stirring at a temperature of 25-40°C for 15-20 hours.
9. The energy storage power supply with high-efficiency heat dissipation function according to claim 1, characterized in that: In S3, washing is performed by washing with water at least three times, and drying is performed in a vacuum oven at 25°C.
Citation Information
Patent Citations
Non-woven fabric polishing wheel containing composite phase change microcapsule and preparation method thereof
CN111360709A
Ceramic-filled PTFE-based composite material for microwave substrate, preparation method and application thereof
CN111961299A